THE THREAT OF RELIGIOUS MODERATION TO RELIGIOUS RADICALISM - Rahman Hakim; Mudofir Mudofir (Universitas Muhammadiyah Surakarta, 2023)
Religious moderation is very important. So that there will always be peace, religious moderation is needed in a pluralistic society. In the midst of the threat of radicalism, which is spreading rapidly and can be dangerous if this understanding of radicalism is embraced by many people, Religious moderation is a religious attitude that takes a fair attitude, is not inclined to be radical, and is not inclined to liberalism. All the arguments in Islam tend to always take a middle attitude, which means balanced. The purpose of this study is to understand and describe religious moderation to prevent the entry of radicalism and liberalism. The results of this literature research show that understanding and applying religious moderation can prevent and protect against being influenced by radicalism and liberalism. Religious moderation will create tolerance, peace and harmony between religious communities. To prevent acts of radicalism and extremism, an understanding of religious moderation is needed that is correct and in accordance with the Al-Qur'an and Al-Hadits